2016
DOI: 10.4172/2329-6887.1000129
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Angiotensin Converting Enzyme Inhibitors during the First Trimester of Pregnancy

Abstract: Background: The direct effects of angiotensin converting enzyme inhibitor (ACEI) medications on the fetus are difficult to determine since these medicines are usually administered to women presenting with high-risk pregnancies. The aim of this study was to provide an overview of the dispensing patterns, demographic characteristics and pregnancy outcomes of women dispensed an ACEI during pregnancy. Methods:Exposed pregnancies were all births in Western Australia, 2002Australia, -2005 where the mother was dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A total of 19 articles, published between 1992 and 2018, were included for data extraction, with 18 articles that enabled quantitative analysis (Figure 1). Characteristics of 19 studies are presented in Table 1 32‐50 : 15 are observational cohort studies, three are case‐control studies, and one is a randomized‐controlled trial, all of which were classified as ‘sufficient quality’ or ‘low risk of bias’ studies (Table S1). Relevant studies were conducted in North America (n = 9), Europe (n = 9), or Australia (n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 articles, published between 1992 and 2018, were included for data extraction, with 18 articles that enabled quantitative analysis (Figure 1). Characteristics of 19 studies are presented in Table 1 32‐50 : 15 are observational cohort studies, three are case‐control studies, and one is a randomized‐controlled trial, all of which were classified as ‘sufficient quality’ or ‘low risk of bias’ studies (Table S1). Relevant studies were conducted in North America (n = 9), Europe (n = 9), or Australia (n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 observational studies reporting on 6234 pregnancies with exposure to ACE‐I or ARB in the first trimester, 4104 pregnancies with exposure to other oral antihypertensives, and 1,872,733 pregnancies without exposure were included in at least one meta‐analysis 4,6–10,19–26 . Table 1 shows the characteristics of all studies included.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the use of ACE‐Is and ARBs in the first trimester did not further increase the risk over and above other antihypertensives and this increased risk was due either to the use of antihypertensives in general or due to the characteristics of the hypertensive women taking them 3 . Since then, at least five additional large population‐based cohort studies have been published on the topic, each showing conflicting results 6–10 …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to several chemicals and pharmaceuticals during pregnancy and early infancy negatively impacts development. Studies estimate a prevalence of 1%-4% of OPEN ACCESS EDITED BY Megha Kumar, Centre for Cellular & Molecular Biology (CCMB), India congenital defects caused by adverse drug effects (Hernandez et al, 2012;Colvin and Walters, 2016;Uguz, 2020). Approximately 55%-90% of women receive at least one prescription drug during pregnancy (Huybrechts et al, 2018;Dathe and Schaefer, 2019).…”
Section: Introductionmentioning
confidence: 99%